Strategi Guru BK dalam Membina Karakter Peserta Didik SMP Negeri 21 Batang Hari - Mita Dwi Agustina (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
The teacher is a special position in the world of education, he is one of the main learning resources because from there students / students receive guidance, teaching and training. The professionalism of a teacher is obtained through special teacher training or training and experience. Then according to the National Education System Law Teachers are qualified teaching staff as teachers, lecturers, counselors, civil service, widyaiswara, tutors, instructors, and participate in organizing education. In line with that the teacher according to the Law on Teachers emphasized that: The teacher is a professional educator with the main task of educating, teaching, guiding, directing, training, evaluating, and evaluating students in early childhood education, formal education, basic education, and secondary education.